The application of administrative empowerment and its impact on the work environment of health institutions in the Sultanate of Oman: a case study - Al-Bulooshi, Ghizlan Ali Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aims to find out the extent to which the application of administrative empowerment, represented by its dimensions: delegation, participation in decision-making, fairness, and credibility, has an impact on the health institutions affiliated to the Ministry of Health in the Sultanate of Oman. The study is based on the Hawthorne theory of human and social relations and was conducted according to the descriptive approach due to its convenience for the purposes of the study. The study community consists of employees of the three administrative levels: (Upper, middle, and lower), the study tool, represented by the questionnaire, was distributed to 440 participants from the sample. Hypotheses were tested and their questions answered to reach results and recommendations that help in the application of administrative empowerment in health institutions. The results of the study confirmed the effectiveness of administrative empowerment and its dimensions on the work environment, and there were statistically significant differences in (delegation) attributed to the gender variable in favor of females and the variable years of experience. The study came up with recommendations, the most important of which are raising awareness of administrative empowerment, and creating a work environment that achieves stability and job security for employees.
Keywords: administrative empowerment; business environment; delegation; decision sharing; fairness; credibility